A Systematic Review and Meta-Analysis of 12-Month Patency After Intervention for Iliofemoral Obstruction Using Dedicated or Non-Dedicated Venous Stents. (June 2022) - Majeed, Ghulam M.; Lodhia, Krishan; Carter, Jemima; Kingdon, Jack; Morris, Rachael I.; Gwozdz, Adam; Saratzis, Athanasios; Saha, Prakash
Background: Endovascular stenting of the deep venous system has been proposed as a method to treat patients with symptomatic iliofemoral outflow obstruction. The purpose of this systematic review and meta-analysis was to compare the effectiveness of this treatment at 1-year following the development of dedicated venous stents. Method and results: We searched MEDLINE and EMBASE for studies evaluating the effectiveness of venous stent placement. Data were extracted by disease pathogenesis: non-thrombotic iliac vein lesions (NIVL), acute thrombotic (DVT), or post-thrombotic syndrome (PTS). Main outcomes included technical success, stent patency at 1 year and symptom relief. A total of 49 studies reporting outcomes in 5154 patients (NIVL, 1431; DVT, 950; PTS, 2773) were included in the meta-analysis. Technical success rates were comparable among groups (97%-100%). There were no periprocedural deaths. Minor bleeding was reported in up to 5% of patients and major bleeding in 0.5% upon intervention. Transient back pain was noted in 55% of PTS patients following intervention. There was significant heterogeneity between studies reporting outcomes in PTS patients. Primary and cumulative patency at 1 year was: NIVL—96% and 100%; DVT—91% and 97%; PTS (stents above the ligament)—77% and 94%, and; PTS (stents across the ligament)—78% and 94%. There were insufficient data to compare patency outcomes of dedicated and nondedicated venous stents in patients with acute DVT. In NIVL and PTS patients, stent patency was comparable at 1 year. There was inconsistency in the use of validated tools for the measurement of symptoms before and after intervention. When reported, venous claudication, improved in 83% of PTS patients and 90% of NIVL patients, and ulcer healing occurred in 80% of PTS patients and 32% of NIVL patients. Conclusions: The first generation of dedicated venous stents perform comparably in terms of patency and clinical outcomes to non-dedicated technologies at 1 year for the treatment of patients with NIVL and PTS. However, significant heterogeneity exists between studies and standardized criteria are urgently needed to report outcomes in patients undergoing deep venous stenting.